Luz e vida: uma proposta de formação continuada de professores - Ramos, Mônica Cunha (2016)
The Course “Light and Life”, which is a product of the present research, is a mediator in helping Science Teachers on how to deal with the Physics classes in secondary school. The aim of the present study was to propose a course which can help Science Teachers with their difficulties in the teaching of Physics in the later years of secondary school, mainly about topics related to the theme Light. The elaboration of the product of this research involved structuring and applying a course of continued formation through the “Fun with Science and Art Museum-DICA, under the theme Light, to Science Teachers of the later years of secondary school, in order to promote an environment of dialogue and problem raising as means of disseminating and discussing the teaching of topics related to Light in the teaching of Sciences. The formation course presented a flexible structure in order to widen the relation between the researcher and the teachers participating in the course, aiming to give an answer to the formative needs of the teachers in relation to the theme proposed. In order to know and discuss the problems and challenges of the teaching of Physics in the Science classes, an approach of insertion and integration of concepts related to the theme Light was conducted, mainly on topics relating to the contents of Physics, Chemistry and Biology, according to the curriculum and the abilities of Sciences worked on in class, through the approach of concepts and practice which approximate the practical and theoretical reality of the formative needs of the teachers involved in this study. This work aimed to understand the relation of Science Teachers with the theme Light and comprehend the relation of the teachers with the present proposal of continued formation promoted by the Museum DICA. The methodological option of this research remained in the domains of qualitative research whose analysis was based on the content analysis. The data collection was carried out through questionnaires and group discussions recorded in audio, besides the participative observation of the researcher. As the research product, the structuring and application of a course of continued formation of Science Teachers of secondary school was proposed, under the thematic Light, and a later restructuring of the course under the same thematic based on the data collected after the application of the referred course, which will be later promoted by the Museum DICA.